A relação entre comportamento de cidadania organizacional e a aprendizagem organizacional: um estudo em uma empresa do setor aéreo civil brasileiro - Passos, Larissa da Silva dos (2023)
At the present study, was analyzed the relationship between organizational citizenship behavior and organizational learning in a brazilian civil airline company. The research done is characterized as descriptive, of quantitative nature, for classify the relationship between the variables, and operationalized through a survey as structured questionnaires. The results were evaluated through the program SPSS 22, with descriptive analysis to identify the profile of the respondents, followed by exploratory factorial analysis, for identify the reliability of the factors. The calculus Cronbach's Alpha was realizated to establish the relationship between the construct factors behavior of organizational citizenship and organizational learning and, applied Pearson's Correlation coefficient was performed. The analyzes evidenced that the higher the level of organizational citizenship behavior, the more employees will be prone to organizational learning. This study, therefore, allowed understanding the interactions between the two constructs, contributing to advance knowledge on the themes and enabling new strategies for the managers of the analyzed company.